China’s Smart Power and the “Community with a Shared Future for Mankind” - Huiling, Luo (Sinología hispánica. China Studies Review, 2024)
This article, being the result of an initial study on the subject, aims to analyze China's smart power in international participation, introduce Chinese theories and perspectives in the new world order, present the achievements obtained in the circumstance of multilateralism. and governance in the fight against COVID-19, deciphering the integral links that international cooperation actions have with the concept of the “Community with a Shared Future for Mankind”, explaining that the Chinese proposal from a multidimensional perspective. It is expected that the approach towards the Chinese model of smart power helps to encourage dialogue between different civilizations and promote international cooperation based on mutual understanding and shared benefit.